New endemic species of manihot (Euphorbiaceae) from serra do tombador in goiás, central Brazil - Moises MendozaF, J.; Simon, Marcelo F.; Reis, Talita S.; Fidelis, Alessandra [UNESP]; Cavalcanti, Taciana B. (Magnolia Press, 2016)
Extensive botanical explorations focused on the taxonomy and phylogeny of the genus Manihot in the Cerrado biome permitted the finding of three new species restricted to Serra do Tombador in the municipality of Cavalcante, Goiás state, of Brazil. Manihot ebracteata, Manihot purpurea and Manihot tombadorensis, are described and illustrated. Morphological characteristics of the new taxa, relationships with closely related species, as well as comments on ecological aspects and natural distribution for each species, are provided.
Keywords: Cerrado; Endemism; Highlands; Taxonomy